Calculus - James Stewart (USA Cole, 2009)
"Success in your calculus course starts here! James Stewart's CALCULUS texts are world-wide best-sellers for a reason: they are clear, accurate, and filled with relevant, real-world examples. With CALCULUS, Sixth Edition, Stewart conveys not only the utility of calculus to help you develop technical competence, but also gives you an appreciation for the intrinsic beauty of the subject. His patient examples and built-in learning aids will help you build your mathematical confidence and achieve your goals in the course!" -Amazon.com.
1. Functions and models -- 2. Limits -- 3. Derivatives -- 4. Applications of differentiation -- 5. Integrals -- 6. Applications of integration -- 7. Inverse functions: exponential, logarithmic and inverse trigonometric functions -- 8. Techniques of integration -- 9. Further applications of integration -- 10. Differential equations -- 11. Parametric equations and polar coordinates -- 12. Infinite sequences and series -- 13. Vectors and the geometry of space -- 14. Vector functions -- 15. Partial derivatives -- 16. Multiple integrals -- 17. Vector calculus -- 18. Second-order differential equations -- Appendices.
Includes index.
Metric International Version
Keywords: Natural Sciences (3GdYdhe GdHMJIs; Calculus -- Textbooks; General